Pattern Of Child Injuries and Its Economic Impact in Bangalore: A Cross-Sectional Study - Chalageri H Vani; Suryanarayana P Suradenapura; Bidare S Nandakumar; Nandagudi S Murthy (Medsci Publications, 2016)
Introduction: Injury, poisoning and other consequences of external cause has accounted to 12.5% of total deaths among children aged 5-14years in India. Very few studies have been conducted about economic impact of child injuries in India. This study focussed on pattern of child injuries and its economic impact in an urban community, Bangalore. Methodology: Cross sectional study was conducted covering 797 children by house-house survey. Pre-tested, semi-structured questionnaire was used. Among injured further details was obtained. Results: Injury prevalence among children aged 0-18years was 62.7/1000 children (95% CI 45.6-79.9); 64% were moderately injured. Median [IQR] age of injured was 9[5-12.25] years and males (60%) had higher injuries. Home was the common place and falls being common external cause. Majority of it occurred while playing(60%). Common time of injury was 2PM and lower limb being the common site. 20% experienced some kind of disability even after 30 days following injury; walking with a limp (10%) being the common disability type. Average cost per injury was Rs 2601 (minimum to maximum was Rs 100- Rs18650)  Conclusions: Prevalence of child injuries 62.7/1000 (95%CI 45.6-79.9). Majority of child injuries occurred at home and falls being common external cause. In child injuries direct cost was higher than the indirect cost.